The Detection of the Types and Contents of Metal Oxides and Ores in The Southern Regions of Al-Gabal Alkhder (Libya) Areas - Hamad Hasan,; Huda Ali,; Hanan Bader,; Mustafa Yousef, (AlQalam Journal of Medical and Applied Sciences, 2025)
This study was carried out on surface and subsurface samples of soil collected from an area extending between Al–Mkhilly to Tobrouk (Eastern North) of Libya. The main aim of this study is to determine the types and contents of metal oxides in the studied samples by using one of the Nano technologies called (X Ray) Fluorescence (XRF). The results of study showed presence of different types of metal oxides including:(Calcium Oxide, Silicon Oxide Magnesium Oxide, Aluminum Oxide, Ferric Oxide, Manganese Oxide, Titanium Oxide, Potassium Oxide, Phosphorus Oxide and Sulfur Oxide) (CaO, SiO2, MgO, Al2O3, Fe2O3, MnO, TiO2, K2O, P2O5, SO3) beside important contents of CaCO3and Mg CO3. The contents of higher detected oxides as (SiO2, Al2O3, Fe2O3, CaO, MgO, CaCO3 and Mg CO3.of the surface samples were ranged as following (14.22 -67.15 %), (2.5 -9.17 %), 1.27 -4.39 %), 11.04 -40.86 %), (1.73 -2.70 %), (19.3 -72.58 %) and (3.60 -5.64 %), respectively. On the other side, their contents in subsurface samples were fluctuated in the ranges of (4.5 -66.95 % ), (1.35 -9.92 %), (0.61 -4.59 %),12.99 -48.96 %), (0.64 -2.83 %), (19.83 -87.05 %), and (1.33 -5.92 %), respectively. Generally, the results of this study showed different values of metal oxides, the main metal Ores may include. Calcite / or Dolomite, Hematite, Quartz, Alumina, Feldspar, these oxides are very important in the industries.